How Damaging is Part-time Employment to a Woman`s Occupational Prospects? - Prowse, V (Nuffield College (University of Oxford), 2005)
This paper investigates the causes of well documented association between part-time employment and low occupational attainment amongst British women. In particular, the relative importance of structural factors and unobserved heterogeneity to the occupational attainment of women who choose to work part-time is investigated. The results indicate that, depending on observed individual characteristics, structural factors explain between 56% and 87% of the difference in the occupational attainment of full-time and part-time workers. The remainder of the difference in the occupational attainment of full-time and part-time workers is attributed to differences in the unobserved characteristics of the two groups of workers.